The Influence Of Service Quality And Customer Satisfaction On Customer Loyalty At The Hotel Best Sport Wisata Batu - Sihaloho, Anggi Simon Alexander; Lestari, Baroroh; Utaminingsih, Arni (Transforma Jurnal Manajemen, 2025)
The rapid development of the tourism sector in Indonesia every year encourages businesses to better understand the needs of tourists. One of the main needs that must be addressed is the provision of comfortable and high quality accommodation. The growing demand for lodging offers both comfort and optimal service has become a key concern for the hospitality industry. This study aims to analyze the effect of service quality and customer satisfaction both partially and simultaneously on customer loyalty at the hotels and villas in BeSt Sport Wisata Batu. This study was a quantitative research. The data collection method was by distributing questionnaires to 60 respondents use purposive sampling technique. The data were analyzed using multiple regression analysis. The results of the analysis showed that service quality had a positive but not significant effect on customer loyalty, while customer satisfaction had a significant effect. The analysis also showed that simultaneously, service quality and customer satisfaction had a positive and significant effect on customer loyalty. These two variables made a major contribution to loyalty, with the remaining influence coming from other factors outside the scope of this study. The results of the study concluded that service quality has no significant effect partially on customer loyalty, while customer satisfaction has a significant effect. Hotel and Villa BeSt Sport Wisata Batu are advised to focus on improving service quality and maintaining customer satisfaction to build loyalty.